Canadian women`s hockey: Concerns and concerns - Locke, M. C.; Karlis, G. (The Sport Journal, 2015)
For Canada hockey is not merely a sport, a game, or a pastime, rather it is a way of life that millions of Canadians are absorbed in. Each year hundreds of Canada`s most talented athletes leave Canada to play hockey in the NCAA. The routine loss of these dynamic individuals not only effects Canadian women`s hockey, but more significantly it impacts Canadian society. The paper provides the current state of condition of the mass exodus of Canadian women`s hockey players to the NCAA while also addressing concerns and challenges. Roughly 400 Canadian women`s hockey players currently play in the NCAA (The Canadian Press, August 21, 2014). The concern is that this number will continue to grow in the future based on the benefits offered by playing in the NCAA versus the CIS. The challenge will undoubtedly become greater for Canada to maintain its top Canadian women`s hockey players in Canada, not only for the betterment of Canadian hockey but also to help sustain cultural pride through its national winter sport.